Virus‐Triggered Autoimmunity Was Associated With Hirschsprung’s Disease Through Activation of Innate Immunity - Zhong, Weiyong; Lan, Chaoting; Chen, Yuqiong; Song, Kai; Ma, Zuyi; Zeng, Jixiao; Huang, Lihua; Zhang, Yan; Zhu, Yun; Xia, Huimin (Journal of immunology research, 2024)
Background: Hirschsprung’s disease (HSCR) is a congenital enteric nervous system (ENS) disorder. Genetics cannot explain most sporadic cases. To explore the relationship between pathogen infection, autoantibodies, innate immune, and HSCR. Methods: Pathogen microarray was conducted in the serum of the prospective neonatal abdominal distension (NAD) cohort, consisting of 56 children followed for at least 6 months until the final diagnosis of HSCR was determined or excluded. We conducted an autoantibody microarray in an HSCR cohort, which is comprised of diagnosed HSCR patients (HSCR) and healthy control subjects (HC). RNA‐seq of colon tissues from aganglionic and ganglionic segments of HSCR patients was performed. Results: Experimental results show that the serum lgM and lgG of enterovirus 71 (EV71) were significantly higher in HSCR than in the gastrointestinal dysfunction (GI) group, with a prediagnose value reaching area under the curve (AUC) over 0.76. We discovered that a group of autoantibodies were significantly higher in HSCR including neuronal pentraxin 1 (NPTX1), amyloid, neuron lysate, and myelin‐associated oligodendrocytic basic protein (MOBP) than that in the HC group. These four autoantibodies could distinguish HSCR from the HC group, with a combined AUC of over 0.90 using both serum IgG and IgM. Further analysis showed that wide activation of innate immune pathways, including toll‐like receptor (TLR) signaling pathway, neutrophil‐to‐lymphocyte ratio (NLR) signaling pathway, red cell distribution width to lymphocyte ratio (RLR) signaling pathway, and cyclic adenosine monophosphate (cAMP) signaling pathway in aganglionic compared to ganglionic segments of HSCR. Conclusion: This study suggested that virus‐triggered autoimmunity may contribute to HSCR through activation of innate immunity, which facilitates the diagnosis and prevention of HSCR.